2021
DOI: 10.1080/1523908x.2021.1893160
|View full text |Cite
|
Sign up to set email alerts
|

The flexibility gamble: challenges for mainstreaming flexible approaches to climate change adaptation

Abstract: Adaptive and flexible approaches based on implementing different measures as new information emerges have been proposed as a way of enabling robustness towards uncertain future climate change. However, the success of flexible approaches in practice depends on the stability of the relevant organizational landscapes. In this paper, we draw upon key insights from the institutional theories of organizations and research on public administration and climate adaptation in Sweden. We argue that potential organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…The challenges for using robust decision support methods in CCA were further explored by [16], who argued that even in a stable country like Sweden, organisational instabilities pose a substantial challenge to the mainstreaming of flexible approaches to climate adaptation. Therefore, the authors concluded that one cannot assume that flexible approaches to climate adaptation will lead to greater robustness, as there is a substantial risk that planned decisions will not be properly implemented and monitored [16]. Finally, a study based on interviews with the civil servants who attended the three workshops when the robust decision support method was used was conducted in 2018 and 2019 [17].…”
Section: Findings From the 2016-2020 Robust Research Programmementioning
confidence: 99%
“…The challenges for using robust decision support methods in CCA were further explored by [16], who argued that even in a stable country like Sweden, organisational instabilities pose a substantial challenge to the mainstreaming of flexible approaches to climate adaptation. Therefore, the authors concluded that one cannot assume that flexible approaches to climate adaptation will lead to greater robustness, as there is a substantial risk that planned decisions will not be properly implemented and monitored [16]. Finally, a study based on interviews with the civil servants who attended the three workshops when the robust decision support method was used was conducted in 2018 and 2019 [17].…”
Section: Findings From the 2016-2020 Robust Research Programmementioning
confidence: 99%
“…• planificar y anticipar múltiples futuros posibles para responder a condiciones cambiantes y consecuencias imprevistas 235,236,237,238 ;…”
Section: Mensaje Clave 315 La Adaptación Requiere Algo Más Que Inform...unclassified